2022
DOI: 10.1017/jfm.2022.388
|View full text |Cite
|
Sign up to set email alerts
|

On the physical nature of the turbulent/turbulent interface

Abstract: The existence of a turbulent/turbulent interface (TTI) has recently been verified in the far wake of a circular cylinder exposed to free-stream turbulence (Kankanwadi & Buxton, J. Fluid Mech., vol. 905, 2020, p. A35). This study aims to understand the physics within the TTI. The wake boundary, approximately 40 diameters downstream of a circular cylinder subjected to grid-generated turbulence, was investigated through simultaneous cinematographic, stereoscopic particle image velocimetry and planar laser ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Hence, the structure of the VSL may not be fully recovered using a high- passive scalar threshold in the quiescent ambient. When, however, background turbulence is present, Kankanwadi & Buxton (2022) concluded that viscosity plays a negligible role within the TTI and that the VSL may not exist at all for cases of intense external turbulence. Here, we are interested in the geometry of the scalar TNTI and TTI outlines, as well as their fractal property, which exists in the inertial range.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the structure of the VSL may not be fully recovered using a high- passive scalar threshold in the quiescent ambient. When, however, background turbulence is present, Kankanwadi & Buxton (2022) concluded that viscosity plays a negligible role within the TTI and that the VSL may not exist at all for cases of intense external turbulence. Here, we are interested in the geometry of the scalar TNTI and TTI outlines, as well as their fractal property, which exists in the inertial range.…”
Section: Resultsmentioning
confidence: 99%
“…However, the interface between a turbulent ambient and a turbulent flow, that is, the turbulent/turbulent interface (TTI), has scarcely been explored, despite its existence in numerous industrial and environmental applications. The presence of the TTI, across which the vorticity and scalar adjust between the surrounding ambient and the turbulent flow akin to the TNTI layer, was only recently shown for a cylindrical wake in a grid-generated turbulent ambient (Kankanwadi & Buxton 2020, 2022). The outer boundary of the TTI or the TNTI layer, denoted as ‘outline’ hereafter, is usually detected by applying a low-magnitude threshold to a flow-dependent scalar field (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…2014). Kankanwadi & Buxton (2022) also demonstrated that the vorticity in the vicinity of the TTI is ‘organised’ in such a way on the wake side of the TTI that it exploits the enhanced strain rates in the interface-normal direction, previously reported for TNTIs (e.g. Cimarelli et al.…”
Section: Introductionmentioning
confidence: 61%
“…a transport of fluid from the wake to the background, as background turbulence intensity was increased. Kankanwadi and Buxton (2022) subsequently showed that the physics of the TTI were fundamentally different to those of the TNTI since the inertial vorticity stretching term ω i s ij ω j , where ω i is the vorticity vector and s ij is the fluctuating rate-of-strain tensor, dominates viscous diffusion. ω i s ij ω j , like all velocity-gradient quantities, is an intermittent quantity, perhaps explaining the importance of intermittency in determining the entrainment rate between two adjacent streams of turbulence.…”
Section: Introductionmentioning
confidence: 99%